Between desires of love and struggles of survival : A study of the Meterse al Rancho Model of intrafamily violence transformation in Colombia - Juanita, Rojas Palacio (2015)
This Master’s thesis is a study of the Meterse al Rancho model of intrafamily violence transformation in Colombia. It critically analyses the pedagogical model and operational strategy developed by the Observatorio para la Paz, to explore its significance in the development of public policies regarding intrafamily violence in Colombia and Latin America. Based in the decolonial option, critical theory, constructivist and constructivism theories, it is argued that Meterse al Rancho model is an alternative pathway to the traditional punitive and psychiatric approaches to tackling family violence. By linking family and peace, Meterse al Rancho focuses on cultural aspects of violence and grassroots education to prevent violence and promote healthy relationships and well-being in families and communities. This model is an innovative example of collaborative work with families, community leaders, universities and the government in processes of cultural transformation based in community education and civic participation. It is revealed, however, that the short-term policy, Haz Paz that supported the development of Meterse al Rancho model does not implement the permanent mechanisms required to produce enduring changes. Furthermore, it is concluded that it is necessary to promote a multi-ethnic and multicultural perspective in public policies so they can go beyond academia and take as a starting point the singularities of all ethnic and cultural Colombian groups. This investigation draws to a close by conjecturing that even though people in contexts vulnerable to violence have strong desires of love, struggles of survival carry weight, and therefore educational projects that do not involve structural transformations might lack substance to effect family transformation processes.